2015
DOI: 10.1007/s00420-015-1090-6
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of musculoskeletal complaints among professional musicians: a systematic review

Abstract: PurposeThis study gives a systematic overview of the literature on the occurrence of musculoskeletal complaints in professional instrumental musicians.MethodsA systematic review. Nine literature databases were searched without time limits on June 25, 2015, also the complete index of the journal Medical Problems of Performing Artists (MPPA) until June 2015 (30;2) was searched, and citation tracking and reference checking of the selected articles were performed. The search consisted of the combination of three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
158
5
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(202 citation statements)
references
References 49 publications
25
158
5
14
Order By: Relevance
“…Niewiele jest także doniesień przedstawiających ewentualne różnice między studentami a profesjonalnymi muzykami dotyczące rozpowszechnienia poszczegól-nych rodzajów dolegliwości [20,21]. Ustalenie, jakie problemy zdrowotne pojawiają się jeszcze przed rozpoczęciem kariery zawodowej, pozwoliłoby na określe-nie potrzeb w zakresie profilaktyki mogącej uchronić przyszłych muzyków-pracowników przed dolegliwościa-mi czasowo lub trwale ograniczającymi ich zdolność do pracy.…”
Section: Wstępunclassified
See 1 more Smart Citation
“…Niewiele jest także doniesień przedstawiających ewentualne różnice między studentami a profesjonalnymi muzykami dotyczące rozpowszechnienia poszczegól-nych rodzajów dolegliwości [20,21]. Ustalenie, jakie problemy zdrowotne pojawiają się jeszcze przed rozpoczęciem kariery zawodowej, pozwoliłoby na określe-nie potrzeb w zakresie profilaktyki mogącej uchronić przyszłych muzyków-pracowników przed dolegliwościa-mi czasowo lub trwale ograniczającymi ich zdolność do pracy.…”
Section: Wstępunclassified
“…Obszarami ciała, w których najczęściej występowały objawy, są szyja lub Tabela 2. Porównanie nasilenia zgłaszanych dolegliwości zdrowotnych związanych z grą na instrumencie występujących w trakcie miesiąca poprzedzającego badanie w grupie studentów i profesjonalistów (porównanie średnich intensywności testem U Manna-Whitneya dla prób niezależnych) kark (79%) oraz ramiona i barki (75%), co potwierdzają także wcześniejsze badania [20]. Podobne rozpowszechnienie dolegliwości mięśniowo-szkieletowych u muzyków wykazano w zagranicznych opracowaniach [6][7][8][9][10].…”
Section: Dolegliwości Mięśniowo-szkieletoweunclassified
“…6 A systematic review found that for a 12-month period the prevalence of musculoskeletal complaints in professional musicians ranged from 41 to 93%. 1 Such problems may entail serious consequences for the musicians' performance, their ability to play the instrument, 3 and ultimately their career. 6 Playing-related disorders of this kind depend on a number identifiable risk factors, as well as associated risk factors about which more scientific knowledge is needed.…”
mentioning
confidence: 99%
“…M usculoskeletal disorders and pain symptoms related to instrumental playing are highly prevalent among musicians, 1,2 and most of these disorders are perceived to be work-related 3 owing to factors such as repetitive movements, static postures, and a stressful and competitive lifestyle. 4,5 Previously, it has been shown that the most prevalent complaints are pain symptoms or injury to the back, neck, and shoulder.…”
mentioning
confidence: 99%
See 1 more Smart Citation